Parental engagement in parent training interventions: findings from the Sinovuyo Caring Families Project - Wessels, Inge Marie (Department of Psychology, 2017)
Background: Poor parental engagement in parent training programmes is problematic as it wastes resources, affects prevention research, and prevent parents from engaging in programming that may benefit them. Understanding predictors of engagement, and how it relates to programme outcomes, is central to developing efficient interventions. There has been very little research into these relationships in low- and middle-income countries, like South Africa, and so this study sought to investigate them in the Sinovuyo Caring Families Programme (SCFP) when it was evaluated via randomised controlled trial (N = 296 parent-child dyads) in South Africa. Methods: Mixed-effects logistic regression models were used to explore baseline predictors of enrolment, attendance, and level of home practice completion among intervention group participants. Additionally, qualitative data on the barriers and facilitators of engagement was collected via semi-structured interviews with 32 of these participants. This data was analysed thematically. Finally, generalised linear mixed methods were used to investigate whether there was an association between attendance and programme outcomes. Results: Lower levels of parenting stress, greater use of physical discipline and lower use of psychological discipline significantly predicted the odds of enrolling. There were no significant predictors of attendance, while there was an effect of facilitation pair on the extent of home practice completion. According to qualitative findings, structural, programmatic, and personal factors all affected engagement in the SCFP. Commonly mentioned barriers included alcohol abuse, financial constraints, and a lack of readiness to change. Facilitators of engagement included a greater sense of motivation and family buy-in. Conclusion: Since higher attendance was associated with greater programme benefits, more effort is needed to support enrolment and retention. Parent training interventions should consider parents' readiness for change. Motivational interviewing approaches at the start may help to increase engagement. Programme implementers should also minimise financial barriers to access, such as by providing transport money before the first session or situating programme venues close to participants' homes. Programmes cannot be viewed in isolation of other community problems, such as alcohol abuse, that may affect participants.